Clinical characteristics of pediatric febrile urinary tract infection in Japan. (March 2021) - Ohnishi, Takuma; Mishima, Yoshinori; Matsuda, Nozomi; Sato, Daisuke; Umino, Daisuke; Yonezawa, Ryuta; Kinoshita, Keiji; Tamura, Kikuko; Mimura, Shigenao; Ariji, Shohei; Maeda, Naonori; Ozaki, Keiko; et al.
Highlights: This is the first study describing the clinical picture of pediatric fUTI in Japan. Febrile UTI has significant male predominance in Japanese infants. E. coli was the first, and Enterococcus was the second most frequent pathogen in fUTI. Enterococcus had a higher rate of VUR and recent antibiotic use than E. coli . The sensitivity of detecting VUR with hydronephrosis was 47.8%. Abstract: Background: Febrile urinary tract infection (fUTI) is the most common serious bacterial infection in children. Despite this, there have been no studies examining the clinical features of pediatric fUTI in Japan. The purpose of this study was to describe the clinical characteristics of fUTI in Japanese children. Methods: A multicenter, retrospective, observational study was conducted at 21 hospitals in Japan. Children under the age of 15 years who were diagnosed with fUTI between 2008 and 2017 were included. The diagnostic criteria were a temperature over 38 °C and the presence of a single bacterial pathogen in urine culture. Patient characteristics were obtained from medical records. Results: In total, 2, 049 children were included in the study. The median age was 5 months, and 59.3% were male. It was found that 87.0% of the males and 53.2% of the females were under 1 year of age. The main causative pathogens identified were Escherichia coli and Enterococcus spp., accounting for 76.6% and 9.8% of infections, respectively. Conclusions: There was a male predominance of fUTI in Japanese children, particularly in infants. Enterococcus spp. were the second most frequent causative pathogen; therefore, Gram staining of urine samples is strongly recommended before initiating antibiotic therapy.